Bioconversão do derivado N-Fenilpiperazínico LASSBio 579, um potencial candidato a protótipo de fármacos - GOMES, Tatiana Caixeta Ferreira (2007)
Bioconversion reactions using filamentous fungi have been extensively exploited and the results obtained are interesting for metabolism studies. The microbial models of animal metabolism, based on the similarity between mammalian metabolism and enzymatic microbial, became a promising alternative for the elucidation of metabolic routes of drugs. In this context, the aim of this work was to promote bioconversion studies with the N-phenylpiperazine derivative LASSBio 579, (1-[1-(4-Chlorophenyl)-1H-pyrazol-4-methyl]-4-phenyl-piperazine), a potencial lead of drugs prototypes. For that HPLC and TLC analytical methodologies were developed and tested for monitoring the bioconversion reactions for this compound. Beneath the documented catalytic activity for different microorganism, fiftteen of filamentous fungi were employed in this study: Absídia blakesleana ATCC 26617; Absídia blakesleana ATCC 10148b; Aspergillus candidus ATCC 2023; Aspergillus ochraceus ATCC 1009; Beauveria bassiana ATCC 7149; Chaetonium indicum LCP 984200; Cunninghamella echinulata ATCC 9244; Cunninghamella echinulata ATCC 9245; Cunninghamella elegans ATCC 36112; Cunninghamella elegans ATCC 26169; Curvularia lunata NRRL 2380; Fusarium roseum ATCC 14717; Mortierella isabelina NRRL 1757; Mucor griseocyanus ATCC 1207a; Rhizopus arrhizus ATCC 11145. Cunninghamella echinulata ATCC 9244 and Aspergillus candidus ATCC 2023 were chosen for studies in semi-preparative scales due to their capacity of producing a bigger variety of metabolites and one of them in greater amount, respectively. Five different derivatives were detected of which three were characterized by NMR and MS (LaBioCon 23, 24 and 25) as hidroxylated, glycosylated and methylpiperazine derivatives respectively, being this last comparative one and identified as being the mammalian derivate of LASSBio 579.